Radiofrequency ablation versus surgical resection in colorectal liver metastasis: insight from an umbrella review - Todeschini, Letizia; Caimano, Miriam; Mattia, Amelia; Cristin, Luca; Martinino, Alessandro; Bianco, Giuseppe; Spoletini, Gabriele; Giovinazzo, Francesco (Frontiers in Oncology, 2025)
IntroductionRadiofrequency ablation (RFA) has emerged as a less invasive alternative to surgical liver resection (LR) for the treatment of colorectal liver metastasis (CRLM) in patients who are not candidates for surgery. This umbrella review aimed to compare the effectiveness of RFA and LR in managing CRLM by synthesizing evidence from multiple meta-analyses.MethodsWe conducted a comprehensive search across Medline, Epistemonikos, Scopus, and the Cochrane Library, focusing on survival outcomes, disease-free survival, perioperative complications, and recurrence rates.ResultsEleven meta-analyses met the inclusion criteria. The results show that LR is superior to RFA in terms of overall survival and disease-free survival for resectable CRLM, although RFA demonstrated lower perioperative complications and mortality. In matched cohorts, the overall survival rates between RFA and LR were comparable. However, RFA was associated with higher intrahepatic recurrence.DiscussionThis review highlights the continued importance of LR for resectable CRLM, while RFA remains a valuable option for non-resectable cases, particularly in patients with higher morbidity. Future studies should focus on more balanced cohort comparisons to better assess the efficacy of these treatments.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024497886, identifier (CRD42024497886).